Pain on Functional Movement Screen Tests and Injury Risk. (November 2015) - Bushman, Timothy T.; Grier, Tyson L.; Canham-Chervak, Michelle C.; Anderson, Morgan K.; North, William J.; Jones, Bruce H.
Abstract : Abstract: Bushman, TT, Grier, TL, Canham-Chervak, MC, Anderson, MK, North, WJ, and Jones, BH. Pain on Functional Movement Screen tests and injury risk. J Strength Cond Res 29(11S): S65–S70, 2015—The Functional Movement Screen (FMS) is a tool intended to evaluate limitations or asymmetries of movement to detect individuals at risk for exercise- and sports-related injury. The purpose was to determine the association and predictive value of specific FMS tests with injury risk in physically active men. Soldiers aged 18–57 years completed the FMS ( n = 2, 476). Demographic and fitness data were collected by survey. Medical record data for any, overuse, and traumatic injury 6 months after the assessment were obtained. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value were calculated along with receiver operator characteristics to determine area under the curve (AUC). Risks, risk ratios, odds ratios (ORs), and 95% confidence intervals were calculated to assess injury risks. Multivariate logistic regression identified that pain on 5 of the 7 tests was associated with greater risk for any injury (OR = 1.50–3.51): deep squat, hurdle step, in-line lunge, trunk stability push-up, and rotary stability. However, FMS registered low sensitivity, PPV, and AUC for all 7 tests for the 3 injury types (2–24% sensitivity, 16–74% PPV, and 50–58% AUC). Although the presence of pain was associated with a higher risk of injury on 5 tests, a low sensitivity, PPV, and AUC were displayed. Therefore, caution is advised when implementing the FMS as a screening tool in an Army or similarly active population as it could lead to prevention and treatment resources being directed toward individuals who are not at greater risk for injury.